EFFECT OF LACTIC ACID FERMENTATION ON THE QUALITY OF BREWER’S SPENT GRAIN AS RUMINANT FEED - Mladenović, Dragana (Journal on Processing and Energy in Agriculture, 2020)
Brewer’s spent grain (BSG) was used in this study as a support for the immobilization of Lactobacillus paracasei NRRL B-4564, thus enabling the recirculation of immobilized biomass in repeated-batch fermentation. The chemical composition and the energy parameters of the fermented and non-fermented BSG were analyzed and compared. Moreover, the probiotic features of L. paracasei were analyzed to examine the possibility of using fermented BSG as a functional ingredient in ruminant diets.The results obtained indicate that the fermented BSG had significantly higher protein and ash contents, as well as a significantly lower content of fiber fractions. Furthermore, the fermentation process increased the BSG energy content. The analysis of probiotic potential revealed a high tolerance of L. paracasei to pH 2.5 and bovine bile, autoaggregation ability and antimicrobial activity, suggesting that the fermented BSG with immobilized microbial biomass can be used as functional feed in ruminant diets.
Keywords: brewer’s spent grain, lactic acid, probiotics, ruminant feed.